2016
DOI: 10.1002/2015wr018130
|View full text |Cite
|
Sign up to set email alerts
|

Integrating cobenefits produced with water quality BMPs into credits markets: Conceptualization and experimental illustration for EPRI's Ohio River Basin Trading

Abstract: This paper develops a method that incorporates the public value for environmental cobenefits when a conservation buyer can purchase water quality credits based on nonmarket valuation results. We demonstrate this approach through an experiment with adult students in a classroom laboratory environment. Our application contributes to the study of individual preference and willingness to pay for cobenefits associated with the production of water quality credits in relation to the Ohio River Basin Trading Project. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…In addition, because the ASC interaction terms are not significant in Columns (2) and (4), the hypothetical bias, if it exists, is unlikely to depend on the respondents' demographic characteristics. The premium interaction terms in Columns (3) and ( 4) are all negatively significant, indicating that in the consequential treatment, respondents are more sensitive to the insurance premium changes, consistent with a large body of literature regarding hypothetical bias (e.g., Liu and Swallow, 2016). In the Appendix S1, Table S5, we have also used the total estimated insurance cost instead of the per-head insurance cost.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, because the ASC interaction terms are not significant in Columns (2) and (4), the hypothetical bias, if it exists, is unlikely to depend on the respondents' demographic characteristics. The premium interaction terms in Columns (3) and ( 4) are all negatively significant, indicating that in the consequential treatment, respondents are more sensitive to the insurance premium changes, consistent with a large body of literature regarding hypothetical bias (e.g., Liu and Swallow, 2016). In the Appendix S1, Table S5, we have also used the total estimated insurance cost instead of the per-head insurance cost.…”
Section: Resultssupporting
confidence: 62%
“…Although CE is more popular, the results are subject to the influence of potential hypothetical bias from stated preference (e.g. Carson and Groves, 2007;Loomis, 2011;Vossler et al, 2012;Bennett and Balcombe, 2012;Liu and Swallow, 2016;Penn and Hu, 2018). Hypothetical bias reflects the difference between hypothetical and real statements of value, where real statements of value can be approximated in experiments with binding economic commitments (List and Gallet, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We are confident that some respondents did believe the survey results would be used to inform policy and thus was policy‐consequential, because we received follow‐up phone calls from survey recipients expressing interest in the potential program being started in their area. However, other authors have found that payment consequentiality (there is at least a chance that payments are real) is required for eliciting responses similar to a real choice (Liu & Swallow, ; Mitani & Flores, ). Because our easement was not payment‐consequential, our estimates may be biased as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…† Despite the scale and importance of EQIP, we lack quantitative evidence on the environmental benefits achieved under the program. One reason is the multiplicity of benefits associated with different types and often even a single type of conservation practices (Liu & Swallow 2016), in addition to the sheer number of practices that have been implemented. ‡ For example, reduced application of nitrogen fertilizer may improve both water quality and air quality.…”
Section: Introductionmentioning
confidence: 99%